Pengaruh Kebutuhan Aktualisasi Diri, Reward Dan Insentif Terhadap Kinerja Karyawan (Studi Koperasi Agro Niaga Jabung) - Cintia Maharani; Hadi Sunaryo; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine and describe the effect of self-actualization, rewards and incentives and employee performance and to determine the effect of self-actualization, rewards and incentives on employee performance simultaneously or partially. This study uses quantitative methods. This type of research is explanatory research.The population of this study were employees of the Jabung Agro Niaga Cooperative Sapronak Unit using snowball sampling as many as 45 respondents. Methods of data collection using a questionnaire.The results of this study indicate that: (1) There is no positive and significant effect of self-actualization on employee performance at the Jabung Agro Niaga Cooperative. (2) There is a positive and significant effect of reward on employee performance at the Jabung Agro Niaga Cooperative. (3) There is a positive and significant effect of incentives on employee performance at the Jabung Agro Niaga Cooperative. Keywords : Self-Actualization, Rewards, Incentives and Employee Performance